A critique of constructivist theory in Science teaching and learning - Almon Shumba; Amasa Philip Ndofirepi; Pesanayi Gwirayi (Kamla Raj Enterprises (KRE), 2023)
The objective of this concept paper is to critique constructivism in teaching and learning. This is a concept paper that reviews and critiques constructivism as epistemology and a learning theory and how teachers can apply this approach in the classroom. Based on research evidence, constructivism contributes significantly to the teaching–learning processes in schools. This concept paper will benefit teachers, learners, policy–makers and researchers in their quest to improve the quality of classroom learning in schools.